Making Marriage Work : A History of Marriage and Divorce in the Twentieth-Century United States - Celello, Kristin (Book collections on Project MUSE., 2009)
"By the end of World War I, the skyrocketing divorce rate in the United States had generated a deep-seated anxiety about marriage. This fear drove middle-class couples to seek advice, both professional and popular, in order to strengthen their relationships. In Making Marriage Work, historian Kristin Celello offers an insightful and wide-ranging account of marriage and divorce in America in the twentieth century, focusing on the development of the idea of marriage as "work." Examining the marriage counseling profession, advice columns in women's magazines, movies, and television shows, Celello describes how professionals and the public worked together to define the nature of marital work throughout the twentieth century. She also demonstrates that the maxim of "working at marriage" often masked important inequalities in regard to men's and women's roles within marriage. Most experts, for instance, assumed that women needed marriage more than men and thus held wives accountable for marital success or failure. Making Marriage Work presents a new interpretation of married life in the United States, illuminating the interaction of marriage and divorce over the century and revealing how the idea that marriage requires work became part of Americans' collective consciousness"--Provided by publisher